2018
DOI: 10.4103/jios.jios_242_17
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Expected Root Position Setup to Monitor Root Angulations and Inclinations during Orthodontic Treatment: A Pilot Study

Abstract: Introduction: Accurate root placement is important for successful orthodontic treatment. Current radiographic techniques to monitor root positions are inaccurate, exhibit poor definition, or use relatively large amounts of radiation in relation to the benefit to the patient. A new methodology that generates an "expected root position" (ERP) setup may be a potential alternative to monitor root position accurately and with minimal radiation. Materials and Methods: This retrospective pilot study included five pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In previous studies comparing root angulation and inclination between expected root position using composite teeth and CBCT, a pilot study with five subjects demonstrated that the buccolingual inclination of maxillary canines required the largest sample size (30 teeth) 15 , 53 . Subsequently, a post hoc power analysis was conducted for the current study with 16 subjects (32 maxillary canines) using G*Power (version 3.1.9.7; Heinrich-Heine-Universität Düsseldorf, Düsseldorf, Germany), specifically for the inclination of maxillary canines.…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies comparing root angulation and inclination between expected root position using composite teeth and CBCT, a pilot study with five subjects demonstrated that the buccolingual inclination of maxillary canines required the largest sample size (30 teeth) 15 , 53 . Subsequently, a post hoc power analysis was conducted for the current study with 16 subjects (32 maxillary canines) using G*Power (version 3.1.9.7; Heinrich-Heine-Universität Düsseldorf, Düsseldorf, Germany), specifically for the inclination of maxillary canines.…”
Section: Methodsmentioning
confidence: 99%